Proanthocyanidins from Uncaria rhynchophylla induced apoptosis in MDA-MB-231 breast cancer cells while enhancing cytotoxic effects of 5-fluorouracil. (September 2017) - Chen, Xiao-Xin; Leung, George Pak-Heng; Zhang, Zhang-Jin; Xiao, Jian-Bo; Lao, Li-Xing; Feng, Feng; Mak, Judith Choi-Wo; Wang, Ying; Sze, Stephen Cho-Wing; Zhang, Kalin Yan-Bo
Abstract: Breast cancer is the most frequently diagnosed cancer and cause of cancer death in women worldwide. Current treatments often result in systematic toxicity and drug resistance. Combinational use of non-toxic phytochemicals with chemotherapeutic agents to enhance the efficacy and reduce toxicity would be one promising approach. In this study, bioactive proanthocyanidins from Uncaria rhynchophylla (UPAs) were isolated and their anti-breast cancer effects alone and in combination with 5- fluorouracil (5-FU) were investigated in MDA-MB-231 breast cancer cells. The results showed that UPAs significantly inhibited cell viability and migration ability in a dose-dependent manner. Moreover, UPAs induced apoptosis in a dose-dependent manner which was associated with increased cellular reactive oxygen species production, loss of mitochondrial membrane potential, increases of Bax/Bcl-2 ratio and levels of cleaved caspase 3. Treatments of the cells with UPAs resulted in an increase in G2/M cell cycle arrest. Cytotoxic effects of 5-FU against MDA-MB-231 cells were enhanced by UPAs. The combination treatment of UPAs and 5-FU for 48 h elicited a synergistic cytotoxic effect on MDA-MB-231 cells. Altogether, these data suggest that UPAs are potential therapeutic agents for breast cancer. Graphical abstract: Highlights: UPAs were mixtures of homo- and heteropolymers of A and B-type propelargonidin, procyanidins, and prodelphinidins. UPAs significantly inhibited MDA-MB-231 cell viability and migration ability in a dose-dependent manner in vitro . UPAs induced oxidative stress and intrinsic apoptosis. Combination treatment of UPAs and 5-FU for 48h elicited a synergistic cytotoxic effect.